Impact of a basic life-saving skills program on refugee students and teachers: a qualitative study - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Sanusi, Zainal Abidin; Che Hasan, Muhammad Kamil; Firdaus, Mohd Khairul Zul Hasymi; Che Abdullah, Che Azunie; Win, Kyu Kyu; Sutrisno, Resti Yulianti (IIUM Press, 2026)
Background: This qualitative post-program evaluation study explored the impact of a basic life-saving skills program on refugee students and teachers from the Rohingya Education Centre in Kuantan, Pahang. Methods: A total of 31 refugee children aged 5–14 years and six teachers participated in focus group discussions to examine knowledge gained, confidence development, and preparedness to respond to life-threatening situations. Results: Thematic analysis, guided by Braun and Clarke’s six-step framework, generated 11 overarching themes, reflecting experiential learning, emotional responses, confidence development, preparedness, and program acceptance. Teachers corroborated student findings, observing improvements in knowledge, skill application, and confidence. Conclusion: Findings suggest that culturally and age-appropriate life-saving skills education can significantly enhance refugee children’s emergency response readiness and promote teacherfacilitated sustainability of safety